Controversy spaces : a model of scientific and philosophical change - Nudler, Oscar (Controversies, 2011)
The notion of controversy space is the key element of the new model of scientific and philosophical change introduced in this book. Devised as an alternative to classical models, the model of Controversy Spaces is a heuristic tool for the reconstruction of processes of conceptual change in the history of science and philosophy. The first chapter of this volume outlines in its initial section the historical trajectory of the dialectical, adversarial approach to the progress of knowledge, from its ancient flourishing and its almost complete oblivion in modernity up to its contemporary revival. T.